Situation Report: Romania, 30 October 1964 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romanian Delegate Disapproves of Soviet-Inspired WFTU Resolution Romanian Delegation to Moscow Celebrations New Soviet Leaders Thank Dej, Maurer Days of Soviet Culture Celebration of Army Day US Business Executive Received by Gheorghiu-Dej Romanian-Bulgarian Economic Cooperation Romanian-GFR Trade Relations